Energy, Transportation and Global Warming - Grammelis, Panagiotis (Green Energy and Technology, 2016)
This book presents a holistic view of climate change by examining a number of energy and transportation technologies and their impact on the climate. High-quality technical research results from specific test-cases around the globe are presented, and developments in global warming are discussed, focusing on current emissions policies from air and maritime transport to fossil fuel applications. Novel technologies such as carbon capture and storage are investigated together with the corresponding process and systems analysis, as well as optimization for mitigating CO2 emissions. Water resources management, waste water treatment, and waste management issues are also covered. Finally, biomass, hydrogen and solar energy applications are presented along with some insights on green buildings. Energy, Transportation and Global Warming is of great interest to researchers in the field of renewable and green energy as well as professionals in climate change management, the transportation sector, and environmental policy.